Exploring modality in analytical exposition texts: a study of senior high school students' writing - Ritonga, Siti Khairani; Sinar, T. Silvana; Zein, T. Thyrhaya (UNIB Press, 2025)
This study examines the application of modality in analytical exposition texts written by senior high school students, focusing on how different modalities convey ideas, judgments, and attitudes. Employing a comprehensive theoretical framework, the research categorizes modality into three types: epistemic (expressing degrees of certainty), deontic (indicating necessity or obligation), and dynamic (reflecting ability or willingness). Data were gathered through a documentation method, analyzing 36 essays written by 11th-grade students in an academic writing class. The analysis identified 77 clauses containing modality, distributed as follows: 42 clauses (54.5%) were epistemic, 11 clauses (14.3%) were deontic, and 24 clauses (31.2%) were dynamic. The dominance of epistemic modality indicates students’ inclination to express degrees of certainty in their arguments, reflecting an awareness of the persuasive demands of analytical exposition. The moderate presence of dynamic modality highlights their ability to convey potential or capability, while the limited use of deontic modality suggests less emphasis on obligation or necessity in their arguments. These findings underscore the critical role of modality in academic writing, particularly in structuring clear and persuasive arguments. This study emphasizes the need for educators to enhance students' understanding and effective application of modality in writing, ensuring greater clarity and precision in their analytical texts. By addressing gaps in students’ use of modality, this research contributes to improving their expressive skills and their ability to tackle complex issues critically. Furthermore, it offers insights into how instructional strategies can better support students in mastering this essential aspect of academic communication.